A Polysaccharide From the Whole Plant of Plantago asiatica L. Enhances the Antitumor Activity of Dendritic Cell-Based Immunotherapy Against Breast Cancer - Gao, Jiafeng; Zhang, Yi-Nan; Cui, Jingwen; Zhang, Jiatong; Ming, Yuexiang; Hao, Zhihui; Xu, Huihao; Cheng, Nan; Zhang, Di; Jin, Yipeng; Lin, Degui; Lin, Jiahao (Frontiers in Pharmacology, 2021)
Dendritic cells (DCs) are the most potent professional antigen-presenting cells (APCs) that mediate T cell immune responses. Breast cancer is one of the most commonly diagnosed diseases and its mortality rate is higher than any other cancer in both human and canine. Plantain polysaccharide (PLP), extracted from the whole plant of Plantago asiatica L., which could promote the maturation of DCs. In this research, we found that PLP could upregulate the maturation of DCs both in vitro and in vivo. PLP activated DCs could stimulate lymphocytes’ proliferation and differentiate naive T cells into cytotoxic T cells. Tumor antigen-specific lymphocytes responses were enhanced by PLP and CIPp canine breast tumor cells lysate-pulsed DCs, PLP and CIPp-cell-lysate jointly stimulated DCs co-cultured with lymphocytes performed the great cytotoxicity on CIPp cells. In 4T1 murine breast tumor model, PLP could control the size of breast tumors and improve immunity by recruiting DCs, macrophages, CD4+ and CD8+ T cells in the tumor microenvironment. These results indicated that PLP could achieve immunotherapeutic effects and improve immunity in the breast tumor model.